UUITE DALAM MELINDUNGI HAK CIPTA SEBAGAI HAK ATAS KEKAYAAN INTELEKTUAL (HKI) DARI CYBERCRIME - Artika Surniandari (Universitas Bina Sarana Informatika, 2016)
As the development of Internet technology is a source of inspiration that are ofinterest because of the easiest and stored therein various kinds of informationrequired for anyone who wants it. Internet as a media announcement is a wisedecision because the internet media works created can be dispersed directlywithout the need for higher promotional costs. however, does not allow anyirresponsible act by hijacking the works or piracy. with qualitative researchmethod is descriptive writers try to describe the meaning of data or phenomenathat can be captured from the observation of these conditions in the communityand associated with the implementation of UUITE in Indonesia. to avoidinfringement of copyright as one of the intellectual property rights laws should beenforced.